2003
DOI: 10.1002/bdd.370
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of uraemic indoxyl sulphate in rats

Abstract: The purpose of the present study was to examine the pharmacokinetic properties of indoxyl sulphate, a harmful uraemic toxin that accumulates during chronic renal failure. The pharmacokinetics and tissue distribution of indoxyl sulphate were examined in normal and 5/6 nephrectomized (CRF) rats. The uptake process of indoxyl sulphate by rat renal cortical slices in vitro was also investigated. Endogenous indoxyl sulphate was found to be mainly distributed in the kidney. The rate of elimination of indoxyl sulphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Experimental CRF was induced by 5/6 Nx (Deguchi et al, 2003). Male Wistar rats (130 -150 g) were anesthetized with sodium pentobarbital (60 mg/kg) by intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental CRF was induced by 5/6 Nx (Deguchi et al, 2003). Male Wistar rats (130 -150 g) were anesthetized with sodium pentobarbital (60 mg/kg) by intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%
“…Under light anesthesia with 60 mg/kg phenobarbital, normal Wistar rats (250 -290 g) and 5/6 Nx rats underwent a surgical procedure in which cannulas were inserted into the femoral vein and artery using polyethylene tubing (polyethylene-50; i.d., 0.58 mm; o.d., 0.9655 mm; BD Biosciences, Parsippany, NJ) (Deguchi et al, 2003 )] as a rapid infusion into the femoral vein. GFR was assumed to be equal to the renal clearance of inulin.…”
Section: Methodsmentioning
confidence: 99%
“…The serum level of IS is known to be markedly elevated in the serum of patients with CKD (the serum concentration 100 :M-1 mM in the case of CKD 12,18,[19][20][21]22,24,24,25,[26][27][28] Albumin Binding (Binding Site) 29 patients versus 0.1-10 :M in healthy subjects), 65,66 and recent clinical studies have shown that IS plays a role in the progression of CKD. [3][4][5] In the intestinal tract, bacteria such as Escherichia coli express tryptophanase, which catalyzes the formation of indole from dietary tryptophan.…”
Section: Indoxyl Sulfatementioning
confidence: 99%
“…Fiveweek-old male rats weighing 140-150 g were subjected to a 5/6 nephrectomy, as previously described. 7,8) Six weeks after the operation, the treated rats showed increased plasma concentrations of creatinine (Ͼ1.0 mg/dl), and reduced levels of creatinine clearance (1.12 approximately 1.24 ml/min). Agematched Sham-operated rats were used for comparison.…”
mentioning
confidence: 99%